TİP 2 DİYABETLİ HASTALARDA PREPTİN DÜZEYİ İLE İNSÜLİN DİRENCİ, RESİSTİN, ADİPONEKTİN VE CRP ARASINDAKİ İLİŞKİ - KALAYCI, MEHMET (Fırat Üniveristesi, 2013)
Diabetes mellitus (DM), hiperglisemi ile karakterize kronik bir hastalık olup, Türkiye dahil dünya genelinde prevalansı hızla artmaktadır. Bu çalışmada; tip 2 diyabetli hastaların serum adiponektin, resistin ve preptin düzeylerinin kontrol grubuna göre nasıl değiştiği ve bu parametreler arasındaki ilişkilerin incelenmesi amaçlanmıştır. Çalışmaya, 82 tip 2 diyabetli hasta ile 65 sağlıklı birey dahil edildi. Tip 2 diabetes mellitus?lu hastalar yeni tanı alan ve tedavi gören olmak üzere iki gruba, diyabet sürelerine göre de; yeni tanı, 1-5 yıl ve 5 yıl üstü olarak 3 gruba ayrıldı. Biyokimyasal parametreler Advia 1800 otoanalizöründe, hormonal parametreler Immulite-2000 cihazında ölçüldü. Serum adiponektin, resistin ve preptin düzeyleri ELISA yöntemiyle ölçüldü. Tip 2 DM?li hastalarda glukoz, HbA1C, insülin, C-peptid, HOMA-IR, total kolesterol, trigliserit, LDL-K, CRP, resistin ve preptin düzeyleri kontrol grubuna göre anlamlı olarak yüksek, adiponektin ve HDL-K düzeyleri ise T2DM?li hastalarda kontrol grubuna göre anlamlı olarak düşük bulundu. Adiponektin düzeyleri ile resistin, CRP, HOMA-IR, insülin ve trigliserit arasında negatif bir ilişki, resistin düzeyleri ile CRP, insülin ve HOMA-IR arasında pozitif bir ilişki, preptin düzeyleri ile insülin, HOMA-IR, HbA1C ve glukoz arasında da pozitif bir ilişki olduğu gözlendi. Sonuç olarak adiponektin, resistin ve preptinin diyabete bağlı olarak değişen konsantrasyonları bu üç hormonun, bu yüzyılda ve gelecek yüzyılda da önemli bir halk sağlığı sorunu olan DM?un patogenezinde rol aldıklarını göstermektedir. Anahtar Kelimeler: Diabetes mellitus, adiponektin, resistin, preptin

Diabetes mellitus is a chronic disease characterized by hyperglycemia and its prevalence is rapidly increasing worldwide including Turkey. In the present study, it was aimed to evaluate how did serum adiponectin do, resistin and preptin levels change in patients with type 2 diabetes mellitus relative to controls and to investigate relationship among these parameters. Eighty-two patients with type 2 diabetes mellitus and 65 healthy controls were included to the study. The patients with type 2 diabetes mellitus were stratified into 2 groups as newly diagnosed and on medication; while they were stratified into 3 groups according to duration of diabetes mellitus as new diagnosis, 1-5 years and longer than 5 years. Biochemical parameters were analyzed by using Advia 1800 auto-analyzer, whereas hormonal parameters by using Immulite-2000 analyzer. Serum adiponectin, resistin and preptin levels were measured by ELISA technique. When compared to controls, HbA1C, insulin, C-peptide, HOMA-IR, total cholesterol, triglyceride, LDL-cholesterol, CRP, resistin and preptin values were significantly higher, while adiponectin and HDL-cholesterol levels were significantly lower in patients with type 2 diabetes mellitus. The adiponectin levels were inversely correlated with resistin, CRP, HOMA-IR, insulin and triglyceride, whereas resistin levels were positively correlated with CRP, insulin and HOMA-IR. In addition, a positive correlation was observed between preptin levels and HOMA-IR, HbA1C and glucose. In conclusion, alteration of adiponectin, resistin and preptin concentrations related to diabetes mellitus shows that these hormones are involved in the pathogenesis of diabetes mellitus which will be an important public health problem in this and subsequent century. Key words: Diabetes mellitus, adiponectin, resistin, preptin
The relationship between preptin level and insulin resistance, resistin, adiponectin and crp in patients with TYPE 2 diabetes mellitus
Keywords: Biyokimya